Proximate composition, functional properties and quantitative analysis of benzoyl peroxide and benzoic acid in wheat flour samples: effect on wheat flour quality - Nisar,Numrah; Mustafa,Faiza; Tahir,Arifa; Qadri,Rashad; Yang,Yaodong; Khan,Muhammad Imran; Wang,Fuyou (PeerJ, 2020)
Background Extensive milling processes have deprived wheat flour from essential nutrients. The objective of the current study was to assess the nutritive quality of commercial wheat flour (soft flour (SF)) through analyses of proximate composition and functional properties as well as quantification of benzoyl peroxide (BPO; added as bleaching agent in the SF) by comparing the results with whole wheat flour (WF; never received any additives). Methods The samples included commercial SF purchased from the local supplier of different flour mills (who use BPO as additive) and a control sample without additives was prepared by grinding the seeds harvested from wheat (Triticum aestivum L.; Inqulab 91) crop grown in the experimental field of University of Agriculture, Faisalabad, under optimized field conditions without any fertilizers and insecticides. Functional properties (including bulk density, water absorption capacity, oil absorption capacity, emulsifying activity, foaming capacity, least gelatinization concentration and gelatinization temperature) and proximate composition (including moisture content, ash contents, crude protein, gluten and starch contents) were determined and compared for all the samples. Benzoyl peroxide (BPO) and Benzoic Acid (BA) quantification was performed through High Performance Liquid Chromatography. Finally dietary intake was estimated for BPO and BA. Results Results showed that SF had lesser fiber, protein and ash contents, whereas, higher damaged starch, fat, gluten and bulk density. A parallel experiment under selected conditions (temperature, time and solute concentration) showed dissociation of BPO into BA soon after the exposure. Observed BA range (13.77 mg/g after 16 h) in SF and exposure level assessment (44.3 ± 1.36 mg/kg/BW) showed higher intake of BA on the consumption of SF. The results revealed the superiority of WF over SF in nutritive qualities as well as free of toxicants such as BA.
Keywords: Benzoyl peroxide; Benzoic acid; Soft flour; Whole wheat flour; High performance; Liquid chromatography